Factors that influence customer satisfaction towards services provided by Sutra Beach Resort & Spa (SBR) / Rosharizan Che Husin - Che Husin, Rosharizan (Faculty of Business and Management, 2008)
The aim of this study was to examine the factors that influence customer satisfaction towards services provided by Sutra Beach Resort & Spa (SBR). There are three factors that been studied, which were: responsiveness, facilities and accessibility. Furthermore, this study also examined the relationship between demographic profiles and customers satisfaction. The objective of this study is to examine the impact of each independent variable to its dependent variable as well as to conclude the relationships exist. In collecting data, the researcher used both the secondary and primary data. Moreover, questionnaires had been used in order to get feedback from customers. Researcher had distributed 100 questionnaires to selected customers who had experienced with Sutra beach Resort & Spa. Then the researcher analyzed the data from questionnaires using Statistical Package for Social Science 14.0 Students Version. The data was interpreted and test using frequency distribution analysis, cross tabulation and reliability analysis. Chi Square, correlation analysis and regression analysis were used in this study to test hypotheses. The findings of this paper suggest that all the factors are significant factors for explaining customers' satisfaction toward services provided by Sutra Beach Resort & Spa. Based from the results obtained in this study, researcher suggests some recommendations that can help Sutra Beach Resort & Spa to improve their current services in order to fulfill their customer satisfaction.